Penerapan Arsitektur Nusantara Sulawesi Selatan Pada Bentuk Desain Creative Hub Kabupaten Wajo - Thamrin, Nurul Fatimah; Marwati, Marwati; Burhanuddin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2022)
Creative hubs form a network that drives the growth of the creative industry at the local level, which then continues to the regional level. A creative hub is a dynamic space that provides more employment opportunities, expands educational services, networking opportunities, and business development, and intensifies innovation in the creative industry. The design of a creative hub by applying the concept of archipelago architecture aims to develop the creative sector in Wajo Regency by designing a creative hub based on local culture. The architectural concept of the archipelago will used to the creative hub form by focusing on the architecture in South Sulawesi. The purpose of the study is to create an innovative center that has the characteristics of South Sulawesi through the method of exploring forms in the concept of building design. The exploration results found compositions that applied the shape of the archipelago of South Sulawesi, especially on the roof and mass composition.